The Solid State 13C NMR Study of Gamma Radiation of Ethylene-Octene Copolymer - Jia, Shaojin; Zhang, Zhenqi; Hou, Xiaotian; He, Tao; Jiang, Pingkai (Journal of Research Updates in Polymer Science, 2014)
Ethylene-octene copolymer (POE) samples exposed to γ-radiation under a series of absorbed doses have been investigated using thermal analysis, sol–gel analysis and solid state 13C nuclear magnetic Resonance (NMR). The chemical shift of POE was assigned and peak evolution as a function of radiation dose was discussed. An obviously evolution is that the peak area of 33.6 ppm decreases as a function of the increase of radiation dose, and at the same time, the peak shape broadens gradually. This indicates that the chain scission occurred between α-C and branch chain C (methine) or between C1 (the sidegroup hexyl) and branch chain C (methane) after radiation. The chain scission is severer with the increase of absorbed dose.The 13C NMR spectra of the corresponding gels confirmed the result. The variation in linewidth of the resonance at 33.6 ppm in samples of POE irradiated to different doses was attributed to information of chain, scission, new cross linking, and crystalline components.